The Relation between Parental Anxiety and Parenting Practices in 12-18 Years old Male Students with Mild Mental Retardation - Shahab Mansouri; Ma'soumeh Pourmohammadreza-Tajrishi; Mohammad Taheri; Seyyed Mahmoud Mirzamani; Masoud Salehi (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The purpose of this study was to determine the relation between parentsʼ child bearing methods parents and school anxiety, regarding to the self-concept as a variable, especially in mentally retarded school students. Materials & Methods: The study Population included all known-available educable mentally retarded students, aged 12-18 years, in Kermanshah. The other entry criteria for the above-mentioned population were the parents' age between 30-55 years and having at least 5-year elementary education. Entire community (157 people) was applied, this way parents of students 30 to 55 years of age and at least fifth of their study, were enrolled After applying these criteria remain Number 125 remained, test your imagination on all students was conducted among 125 students, then 83 patients were available. And then by parents child rearing styles test methods and test anxiety of students by teachers of the school was completed. Obtained data with statistical tests, including tests Kolmogorov-Smirnov (for study being normal data distribution), Pearson and Spearman correlation (for relation between variables) and Covariance analysis tests were analyzed. Results: Results showed that children husbandry practices powerful father (P=0.002) and mother (P=0.001) a significant negative relationship with school anxiety. The autocratic style husbandry child's father (P=0.009) and mother (P=0.020) a significant positive relationship with school anxiety. In addition, simple husbandry practices lighter child's father (P=0.319) and mother (P=0.452) have a significant relationship with school anxiety and determined that a significant effect on anxiety self concept school students are mental (P=0.004). Conclusion: Statistical test results showed child rearing methods parents ways anxious school students are effective but moderate effect on self concept child rearing parents practices is an important than part of school anxiety. This means that students who have strong self concept less students who are weak self concept, anxiety, school experience.